The therapeutic space and doctor–parent relationship in paediatrics: trainees' experiences and perspectives. (3rd December 2018) - Arzuaga, Bonnie H.; Petty, Carter; Janvier, Annie
Abstract: Aim: To explore paediatric trainees' experiences and perspectives regarding interactions and relationships between physicians and patients' parents. Methods: Email survey was sent to AAP Section of Pediatric Trainees members. Trainees were asked about 40 interactions with parents as well as perceived benefits/risks and potential influences. Analysis of associations between variables and perspectives/experiences used chi‐square and Fisher exact. Results: Three hundred and seventy surveys were completed. Respondents participated in a median of nine interactions (IQR 7–13; range 0–37): 99.7% participated in at least one; 52% in 5–10; 41% in >10. 50% reported refusing to participate in at least one interaction following parental request; 8% refused 5–10; 1% refused >10. Electronic communication/social media domain had highest refusals and most interactions respondents believed should never be allowed. 94% agreed that interactions may be beneficial to providers: 75% identified at least one benefit; 86% one risk. Respondents who are parents or female reported increased interactions. Conclusion: A variety of interactions with patient's parents are common amongst paediatric trainees, who identify risks and benefits. Disagreements relative to acceptability of certain interactions points to the need for additional research. A reflective educational approach, rather than a prescriptive one, may help trainees better manage these relationships.